Liver disease associated with intestinal failure in the small bowel syndrome - Kemp,Rafael (2006)
The introduction of the Total Parenteral Nutrition (TPN) has given rise to a new hope in the treatment of intestinal failure (LF) associated with the Short Bowel Syndrome (SBS). However, together with the TPN and the increase of survival of these patients, new problems and questions have emerged, as well as new therapeutical procedures. Taking into consideration this emerging reality, this paper has the purpose to undertake a review of current concepts and available treatments for patients with IF associated-liver disease. Although TPN provides an increase of survival of patients with intestinal failure, it is a potential source of complication such as: septicemia, hyperglycemia, venous thrombosis and liver disease. There are several hypothesis conceived to explain the liver disease associated to intestinal failure, however the only definite treatment as a potential to reverse the non-cirrhotic liver disease is the small intestine transplantation. Despite indications for intestine transplantation are not entirely defined in literature, the trend is its early indication in high-risk patients, preserving the liver integrity and preventing the eventual need of both liver and intestine transplantations altogether.